THE ROLE AND RESPONSIBILITY OF A NOTARY TO CANCELLATION OF THE DUE TO THE WILL HAS BEEN DONE - Muhammad Hakiki Dharmawan; Lathifah Hanim; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study as follows: 1) To analyze and clarify the roles and responsibilities towards the cancellation of a notary deed will have been made before. 2) To analyze and explain the obligations to be performed by a notary deed after the will was made. 3) To analyze and explain the responsibilities of a notary deed will made beforeThe research method used is juridical Normative and specifications in this research include descriptive.Now the sources and types of data in this research is primary data obtained from field studies and interviews. And secondary data obtained from the literature. Based on the results of research thatThe role and responsibilities of a notary to act that is canceled if one party has been in default and notaries have met the terms of a formal deed, the notary is not responsible or may not be deducted on the cancellation of the deed. Shall notify all acts of will (testament acte) made to the Central Register of Wills Section (DPW) and Universal Heritage (BHP) both open testament (openbaar testament), written testament (olographis testament), as well as a closed or secret testament. If the act of will (testament ACTE) is not registered then it will not happen binding. Moreover, notaries are also obliged to report or inform one's will on a five (5) days of the first week of each month. If you do not report it, then the act is not applicable as authentic documents, or in other words the act is only valid as a deed under hand, can even be declared null and void. Responsibility of the Deed of Wills Made in front of him is a) moral responsibility, b) ethical responsibility, c) a legal obligation, consisting of two (2) terms: 1. In terms of formal 2. in terms of material. Act against the will (testament acte) made in front of him, read it in the presence of a notary is responsible for the witnesses.Keywords : Roles, Responsibilities, Notary Act, Wills